The International Consortium for Quality Research on Dietary Sodium/Salt (TRUE) position statement on the use of 24‐hour, spot, and short duration (<24 hours) timed urine collections to assess dietary sodium intake. Issue 6 (14th May 2019) - Campbell, Norm R. C.; He, Feng J.; Tan, Monique; Cappuccio, Francesco P.; Neal, Bruce; Woodward, Mark; Cogswell, Mary E.; McLean, Rachael; Arcand, Joanne; MacGregor, Graham; Whelton, Paul; Jula, Antti; et al.
Abstract: The International Consortium for Quality Research on Dietary Sodium/Salt (TRUE) is a coalition of intentional and national health and scientific organizations formed because of concerns low‐quality research methods were creating controversy regarding dietary salt reduction. One of the main sources of controversy is believed related to errors in estimating sodium intake with urine studies. The recommendations and positions in this manuscript were generated following a series of systematic reviews and analyses by experts in hypertension, nutrition, statistics, and dietary sodium. To assess the population's current 24‐hour dietary sodium ingestion, single complete 24‐hour urine samples, collected over a series of days from a representative population sample, were recommended. To accurately estimate usual dietary sodium at the individual level, at least 3 non‐consecutive complete 24‐hour urine collections obtained over a series of days that reflect the usual short‐term variations in dietary pattern were recommended. Multiple 24‐hour urine collections over several years were recommended to estimate an individual's usual long‐term sodium intake. The role of single spot or short duration timed urine collections in assessing population average sodium intake requires more research. Single or multiple spot or short duration timed urine collections are not recommended for assessing an individual's sodium intake especially in relationship to health outcomes. The recommendations should be applied by scientific review committees, granting agencies, editors and journal reviewers, investigators, policymakers, and those developing and creating dietary sodium recommendations. Low‐quality research on dietary sodium/salt should not be funded, conducted, or published.